CONNECTING BY DIFFERENCES: CREATING SPATIAL CONTINUITY FROM DIFFERENT LEVELS OF MEDIATIONS - Marina Bonnici; Eun Kim (Journal of Synergy Landscape, 2021)
The area is located in Città studi, on the edge of the dense complex of Politecnico di Milano and the large green space Giuriati Sports Field: two areas have no spatial continuity. The design intention is to establish a mutual relationship between campus and the urban context. By working on the concept of the threshold space as an opportunity for mediation, we were able to envision public and open spaces that interact with the city. The design of the new complex is based on a principle of balance between horizontality (public sphere) and verticality (private sphere), taking into consideration how, according to the principle of urban mixité, the relationship between public, social, working and private life will take on a new shape. The complex will therefore represent a transition between the urban setting and the rest of the campus. Its interior is based on the use of different threshold and mediation levels: these are configured as a gradual sequence starting from the more urban context of the work space, which is connected to the residence through the underground, to the exhibition and archive centre, which embodies the reciprocal relationship between city and campus, to the more private sphere of the residential complex, envisioned as a mix of domestic and work spaces that is reflected in each individual housing unit as well as the common areas. The dissertation was built upon a research on the formation of the threshold space, paying particular attention to the spatial continuity between indoors and outdoors.